Dementia in Nursing Homes - Schüssler, Sandra; Lohrmann, Christa (Springer International Publishing : Imprint: Springer, 2017)
Written by leading international experts, this book discusses the latest advances in the field of dementia in nursing homes. The topics and findings covered are based on their survey and on a scientific literature review. Dementia is spreading worldwide, placing a growing burden on healthcare systems and caregivers, as well as those affected. With increasing and complex care needs, nursing home admission is often necessary. Globally, over half of nursing home residents suffer from dementia. The book provides essential information on the most important issues in dementia in nursing homes today, including meaningful activities, patient-/person-centered care, psychosocial interventions, challenging behavior, inclusion and support of family members, pain, staff training and education, communication, polypharmacy, quality of life, end-of-life care and advanced care planning, depression, delirium, multidisciplinary approaches, physical restraints and care dependency. Each topic is covered by an international expert in dementia. As such, the book will appeal to professional nurses, nursing scientists, nursing students, other healthcare professionals, and to a broad readership, and will provide a valuable resource for those working in nursing homes, as well as researchers in the field.
Keywords: Medicine.; Geriatrics.; Nursing.; Pain medicine.; Psychiatry.; Behavioral therapy.; Medical research.; Quality of life.; elektronické knihy; electronic books